A narrative review exploring the association between hypothyroidism and thoracic aortic diseases - Mohammad Hamzah, BS; Fatima Al-Maaz, BS; Ahmad Chalhoub, BS; Rita Nemr, MD (JVS-Vascular Insights, 2025)
Background: Thoracic aortic aneurysms (TAA) and aortic dissections (AD) are recognized as one of the leading causes of death in developed countries. Although mortality decreases if at-risk individuals are diagnosed early, on thorough screening, many fail to seek the proper preventive interventions timely. Genetic predisposition, smoking, and hypertension are well-known risk factors for highly lethal aortic aneurysmal rupture or dissection. Hypothyroidism has also been described extensively in the literature as a possible risk factor directly related to the origin of TAA and dissection. Numerous studies have proposed a pathophysiological role for hypothyroidism in the development of TAA and AD, although this role is still not fully understood. This scoping review sought human and animal studies to examine the relationship between hypothyroidism and thoracic aortic diseases. Methods: A search in PubMed, Web of Science, and Scopus using the terms “aortic dissection,” “aorta,” “aortic aneurysm,” and “hypothyroidism” yielded 907 articles, although only 9 were relevant to this study topic and criteria. Results: The included articles discuss thoracic aortic diseases as potential risk factors for TAA and dissection. A low thyroid hormone level might be a negative prognostic indicator after acute AD. Conclusions: Establishing a link between hypothyroidism and thoracic aortic diseases could improve clinical practice through the development of screening strategies for thyroid function in patients with thoracic aortic diseases, thereby reducing postoperative mortality rates.